Ionic Liquid Based Polymer Gel Electrolytes for Use with Germanium Thin Film Anodes in Lithium Ion Batteries. Issue 12 (13th December 2019) - McGrath, Louise M.; Jones, John; Carey, Edwin; Rohan, James F.
Abstract: Thermally stable, flexible polymer gel electrolytes with high ionic conductivity are prepared by mixing the ionic liquid 1‐butyl‐1‐methylpyrrolidinium bis(trifluoromethylsulfonyl)imide (C4 mpyrTFSI), LiTFSI and poly(vinylidene difluoride‐co‐hexafluoropropylene (PVDF‐HFP). FT‐IR and Raman spectroscopy show that an amorphous film is obtained for high (60 %) C4 mpyrTFSI contents. Thermogravimetric analysis (TGA) confirms that the polymer gels are stable below ∼300 °C in both nitrogen and air environments. Ionic conductivity of 1.9×10 −3 S cm −2 at room temperature is achieved for the 60 % ionic liquid loaded gel. Germanium (Ge) anodes maintain a coulombic efficiency above 95 % after 90 cycles in potential cycling tests with the 60 % C4 mpyrTFSI polymer gel. Abstract : Flexible polymer gel electrolytes containing the ionic liquid C4 mpyrTFSI were synthesized. Gels with the optimised ionic liquid content exhibited ionic conductivities comparable to organic solvent electrolytes. These gels enable stable lithium ion cycling in germanium.